PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR - Masriah Masriah; Sri Utaminingsih; Slamet Utomo (Universitas Muria Kudus, 2021)
The purpose of this research was to determine: (1) the effect of the Problem Based Learning learning model on Mathematics for Elementary School students' fraction material in Demak District, (2) the effect of the Discovery Learning learning model on Mathematics subject fraction material for elementary school students in Demak District, and ( 3) differences the influence the Problem Based Learning and Discovery Learning models on Mathematics subject fractions of elementary school students in Demak District. The research method used a quasi experimental design , with a population of all students in class I V SD Demak sub-district from 53 SD, totaling1,661 students. The research sample, class 4 SD Negeri Kadilangu 1, Demak Regency, as an experimental class with a total of 34 students and grade IV SD Negeri Bintoro 9 with a total of 35 students. Meanwhile, the control class was the grade IV student of SD Negeri Kadilangu 2 with a total of 31 students